Topical Potential Effect of Sodium Nitroprusside in Induced Oculohypertension in Rabbits - Saja Majeed Shareef; Mustafa Ghazi Al-Abbassi; Ahmed Ismael Alshather; Dalia Abd Al Kader Shakur (College of Pharmacy / Mustansiriyah University, 2019)
Glaucoma is an optic neuropathy known by slow degenerative structural changes seen in retinal ganglion cells and the optic nerve head. Elevation in intraocular pressure caused by     imbalance between the production of A queous humor and the drainage of this liquid through the trabecular meshwork. Nitric oxide donors being evaluated as a novel way to impact the progression of glaucoma by increasing the conventional outflow, hence lowering intraocular pressure. The aim of study was to evaluate the potential effect of topical sodium nitroprusside in glaucomatous rabbits.  Thirty-two rabbits were used and distributed into four groups include: normal group, glaucoma induced group, sodium nitroprusside (SNP) group and timolol group. The treatment was given twice daily: at 9:00 a.m. and at 1:00 p.m. for 12 day. The intraocular pressure was recorded two times a day: at 9:00 a.m. and at 12:00 p.m. The intraocular pressure, nitrite level, endothelial nitric oxide synthase and the histology of ciliary body were measured. The results revealed a high significant decrease in intraocular pressure and no significant difference in nitrite level while a high significant elevation in endothelial nitric oxide synthase with improvement in the histology of ciliary bodies.